The Arabic medication-related burden quality of life (MRB-QoL) tool: Cross-cultural adaptation and content validation - Sundos Q. Al-Ebrahim; Jeff Harrison; Timothy F. Chen; Hamzah Alzubaidi; Mohammed A. Mohammed (Exploratory Research in Clinical and Social Pharmacy)
Background: The Medication-Related Burden Quality of Life (MRB-QoL) is a 31-item valid and reliable patient-reported measure of medicine burden on functioning and well-being in people with long-term conditions (LTC). Objectives: To translate, culturally adapt, and content validate the MRB-QoL into Arabic. Methods: A rigorous approach to cross-cultural adaptation proposed by the International Society for Pharmacoeconomics and Outcomes Research (ISPOR) guideline was followed. After 3 forward translations and 2 backward translations, a multidisciplinary expert panel assessed the content validity (CV) of the items through a 2-round e-modified Delphi method followed by two-step cognitive debriefings with patients with LTC using think-aloud and probing techniques. An item-content validity index (I-CVI) score of ≥0.78 was considered acceptable. The original questionnaire developers and other researchers, as members of the review committee, reviewed and approved the Arabic version. Results: Five semantic and 3 cultural translation discrepancies were identified and resolved by rewording the items. The 2 backward translations did not reveal significant problems, and equivalence to the original tool was confirmed following committee review. The Arabic version showed acceptable CV parameters. E-modified Delphi involved 9 experts in round one and 7 in round 2. The I-CVI scores ranged from 0.67 to 1.0, and agreement was reached after 2 rounds. The CVI for the final version of the MRB-QoL was 0.96. Expert panel review showed that the MRB-QoL-Arabic version is relevant (CVI = 0.92), important (CVI = 0.97), clear (CVI = 0.98), and comprehensive in measuring the burden of medicines. Data from 5 cognitive interviews showed that items and concepts included in the Arabic version of the MRB-QoL are relevant to the targeted sample, clear, and easy to understand. Conclusion: The MRB-QoL Arabic version was developed and content validated. However, further evaluation of its other psychometric properties is necessary before it can be utilized in clinical and research settings. Using this tool will enable a more accurate understanding of the effects of treatment burden on patient well-being, thereby guiding care toward minimally disruptive medicine.